Memetics and disinformation through images of the contemporary media ecosystem - Porto, Denis Reno [UNESP]; Ito, Liliane De Lucena [UNESP] (Centro Int Estudios Superiores Comunicacion Amer Latina-ciespal, 2024)
We live in an image society, where the use of iconic and visual devices has gained strength. Furthermore, it is a society where citizens produce their own content and circulate it through their social media channels, disseminating ideas, philosophies, thoughts and, in some cases, misinformation. From there arises memetics, the subject of the study, and its insertion into the contemporary media ecosystem, since memetics and massive misinformation result from the media ecology in which we currently live. For the article, we basically worked with bibliographic research and, from that, we developed a reflection on memetics in the contemporary media ecosystem, as well as its potential connection with misinformation. We hope that the article, which has an exploratory nature, can offer support for various other investigations.
Keywords: Communication; Memetics; media ecology; Imagistic Narratives; Disinformation